The volatile anesthetic isoflurane differentially inhibits voltage-gated sodium channel currents between pyramidal and parvalbumin neurons in the prefrontal cortex - Qiu, Jingxuan; Yang, Yaoxin; Liu, Jin; Zhao, Wenling; Li, Qian; Zhu, Tao; Liang, Peng; Zhou, Cheng (Frontiers in Neural Circuits, 2023)
How volatile anesthetics work remains elusive. Modulations on synaptic neurotransmission are the direct cellular mechanism of volatile anesthetics in central nervous system. Volatile anesthetics such as isoflurane may reduce the neuronal interaction by differentially inhibiting neurotransmissions between GABAergic and glutamatergic synaptics. Presynaptic voltage-dependent sodium channels (Nav), which strictly coupled with synaptic vesicle exocytosis, are inhibited by volatile anesthetics; and may contribute to the selectivity of isoflurane between GABAergic and glutamatergic synaptics. However, it is still unknown how isoflurane at clinical concentrations differentially modulates Nav currents between excitatory and inhibitory neurons in tissue level. In this study, electrophysiological recording was applied in cortex slices to investigate the effects of isoflurane on Nav between parvalbumin (PV+) and pyramidal neurons in PV-cre-tdTomato and/or vglut2-cre-tdTomato mice. As a result, isoflurane at clinically relevant concentration produced a hyperpolarizing shift in the voltage-dependent inactivation; and slowed the recovery time-course from the fast inactivation in both cellular subtypes. Because the voltage of half-maximal inactivation was significantly depolarized in PV+ neurons than that of pyramidal neurons; therefore, isoflurane inhibited the peak Nav currents in pyramidal neurons more potently than those of PV+ neurons (35.95% ± 13.32% vs. 19.24% ± 16.04%, P = 0.036 by Mann-Whitney test). In conclusion, isoflurane differentially inhibits Nav currents between pyramidal and PV+ neurons in cortex, which may contributes to the preferentially suppression of glutamate release than GABA release, resulting to the net depression of excitatory-inhibitory circuits in cortex.